PATHOPHYSIOLOGY OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS AND DRUG RESISTANCE - Ataa Elias Karum; Soha Jassim Mohammed; Sanaa Adnan Abdul Hussein; Israa Saleh Ahmed; Marwa Muhammad Odeh (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Methicillin- resistant Staphylococcus aureus (MRSA) is one of the most successful modern pathogens of community and hospital acquired bacterial infections. MRSA can lead to diverse infection such as bacteremia, endocarditis, skin and soft tissue infections, bone and joint infections and hospital- acquired infections . As well as genetically diverse, the epidemiology of MRSA is primarily characterized by the serial emergence of epidemic strains. MRSA still poses a formidable clinical threat, with persistently high morbidity and mortality. They are also becoming increasingly multi-drug resistant and have recently developed resistance to vancomycin, which has been used successfully to treat MRSA for many years . Successful treatment remains challenging and requires the evaluation of novel antimicrobials. In Conclusion the emergence of CA-MRSA and VRSA isolates is changing the management of clinical infections potentially caused by S. aureus. Rapid methods for accurate detection of MRSA are needed to promptly identify patients and implement contact precautions as well as appropriate treatment. Molecular genotyping techniques have an important role in evaluating possible outbreaks and for understanding of the emergence and evolution of MRSA strains